Aphid‐repellent, ladybug‐attraction activities, and binding mechanism of methyl salicylate derivatives containing geraniol moiety. Issue 2 (3rd November 2022) - Yang, Zhao‐Kai; Qu, Cheng; Pan, Shi‐Xiang; Liu, Yan; Shi, Zhuo; Luo, Chen; Qin, Yao‐Guo; Yang, Xin‐Ling
Abstract: BACKGROUND: Aphids have been mainly controlled by traditional chemical insecticides, resulting in unamiable risk to the environment over the last decades. Push–pull strategy is regarded as a promising eco‐friendly approach for aphid management through repelling aphid away and attracting their natural enemy. Methyl salicylate (MeSA), one of typical HIPVs (herbivore‐induced plant volatiles), can repel aphids and attract ladybugs. Our previous studies discovered a new lead compound 3e, a salicylate‐substituted carboxyl ( E )‐ β ‐farnesene derivative that had effective aphid‐repellent activity. However, whether 3e has attractive activity to ladybug like MeSA is unknown. Meanwhile, to discover a new derivative for both deterring aphid and recruiting ladybug is meaningful for green control of aphids. RESULTS: Through the structural optimization of 3e, 14 new derivatives were designed and synthesized. Among them, compounds 4e and 4i had good aphid ( Acyrthosiphon pisum ) repellent activity, and compounds 3e, 4e and 4i had significant ladybug ( Harmonia axyridis ) attractive activity to males. Particularly, 4i exhibited manifest attractive effect on the females as well. Binding mechanism showed that 4i not only bound effectively with the aphid ( Acyrthosiphon pisum ) target Apis OBP9 thanks to its multiple hydrophobic interactions and hydrogen‐bond, but also had strong binding affinity with ladybug target Haxy OBP15 due to the suitable steric space. Additionally, 4i displayed low toxicity to bee Apis mellifera . CONCLUSION: Compound 3e does exhibit attractive activity to male ladybug as MeSA. However, the new derivative 4i, with both pleasant aphid‐repellent and ladybug‐attraction activities, can be considered as a novel potential push–pull candidate for aphid control in sustainable agriculture. © 2022 Society of Chemical Industry. Abstract : A series of novel methyl salicylate derivatives (4a‐4n ) containing geraniol were designed and synthesized. Compound 4i, with both significant aphid‐repellent and ladybug‐attraction activities, can be considered as a novel potential push–pull agent for eco‐friendly aphid control.